Genetic Polymorphism of Growth Hormone Gene Exon-4 in Surti and Mehsani Goats by PCR-RFLP - Bayan, Jyotishree; Khardi, Vishnu; Rani, Umed; Janmeda, Mamta; Tyagi, Kuldeep; Dangar, Nikhil; Pandya, Gaurav (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
The present investigation was planned to study growth hormone (GH) gene exon-4 polymorphism using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) in Surti and Mehsani goats. GH gene exon-4 region was found to be monomorphic on restriction digestion with HaeIII, which revealed only one genotype CC in both Surti and Mehsani goat breeds. The allelic frequency of C was 1.00 in both the breeds of goats with absence of D allele. meat purpose. Goat has distinct social, economical, managerial and biological advantages over other livestock species and often termed as the “Poor man’s cow. Out of the 28 defined goat breeds in India (NBAGR), 5 breeds namely, Surti, Mehsani, Kutchi, Zalawadi and Gohilwadi are native to Gujarat. The Surti and Mehsani goat breeds are found in two different parts of Gujarat, Surat and Mehsana respectively, kept for both milk and Animals with high milk yield reveal superior Growth Hormone (GH) average levels than animals with lower production, mainely during peak lactation (Reinecke et al., 1993). GH gene, with its functional and positional potential, has been widely used as a molecular marker in several livestock species including the cattle, sheep and goat. GH gene may be used as a candidate gene for studying its polymorphism